Gun Homicide Research: What We Know and Where We Need to Go. Issue 1 (February 2022) - Buggs, Shani; Zeoli, April M.
Guns are used in the majority of homicides in the United States, making the problem of homicide largely a problem of gun violence. This article presents three types of gun homicide (mass shootings, intimate partner homicide, and community gun violence), and briefly discusses the state of knowledge on their risk factors and promising interventions. Future directions for research are presented, focusing on examining differential implementation and impacts of interventions by racialized groups and communities, as well as interrogating conventional approaches and methodologies.